2022
DOI: 10.1002/vetr.2482
|View full text |Cite
|
Sign up to set email alerts
|

Owner perspectives on the impact of veterinary surgeons upon their decision making in the management of dogs with idiopathic epilepsy

Abstract: Background Idiopathic epilepsy is a prevalent canine condition that can be challenging to manage. A positive vet–owner relationship contributes to satisfaction and compliance, but its impact on management is unclear. The aim of this study was to investigate owner perspectives about the impact of veterinary surgeons on decision making and management. Methods Qualitative methods were utilised, and semi‐structured interviews were completed with 21 owners of dogs with epilepsy who lived in England. Transcripts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Just recently, it was observed that the relationship between the owner and veterinary surgeon plays a role in the management of dogs with IE ( 36 ). These six cases illustrate that we also need to take into account the domestic situation of the dog.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just recently, it was observed that the relationship between the owner and veterinary surgeon plays a role in the management of dogs with IE ( 36 ). These six cases illustrate that we also need to take into account the domestic situation of the dog.…”
Section: Discussionmentioning
confidence: 99%
“…BCs have a strong focus on their owners, and this may have a clear influence on their and their owners' stress level. Importantly, veterinarians should be aware of their own impact on owners of dogs with IE ( 36 ).…”
Section: Introductionmentioning
confidence: 99%